THE PROBLEM OF STUDYING THE VOCABULARY OF WOMEN'S CLOTHES AND FASHION IN LINGUISTICS - Tillaboyeva Gulrukh Sakhibbek kizi (Western European Studies, 2024)
In this article, the issue of studying the vocabulary of women's clothing and fashion in linguistics is scientifically researched.
Keywords: Clothes; shoes; hats